2016
DOI: 10.1111/febs.13927
|View full text |Cite
|
Sign up to set email alerts
|

Creation of active TIM barrel enzymes through genetic fusion of half‐barrel domain constructs derived from two distantly related glycosyl hydrolases

Abstract: Pyrococcus furiosus beta-glucosidase (CelB, EC: 3.2.1.21). Clostridium cellulolyticum endoglucanase A (CelCCA, EC: 3.2.1.4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…One reason for poor binding of SDS can be the recalcitrance of the protein to unfold under standard conditions of sample preparation for SDS‐PAGE. A structurally ultra‐stable protein derived from a hyperthermophile can fail to unfold within 2‐3 min, or even hours, of boiling in standard SLB, or even under harsher conditions as reported for proteins from Pyrococcus furiosus . (ii) High innate negative charge content .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for poor binding of SDS can be the recalcitrance of the protein to unfold under standard conditions of sample preparation for SDS‐PAGE. A structurally ultra‐stable protein derived from a hyperthermophile can fail to unfold within 2‐3 min, or even hours, of boiling in standard SLB, or even under harsher conditions as reported for proteins from Pyrococcus furiosus . (ii) High innate negative charge content .…”
Section: Discussionmentioning
confidence: 99%
“…Highly acidic proteins can be expected to repel SDS. In a recent series of papers examining the binding of SDS to proteins, it has been observed that the overall charged status of a protein is the primary determinant of the ease with which it can be approached by SDS molecules . If the pH of a protein's environment is well below its pI, it protein possesses an overall positive charge, and is easily approached by SDS.…”
Section: Discussionmentioning
confidence: 99%
“…Protein structure and function evolve through sequence changes, substitutions, duplications, insertions, and deletions, including rearrangement or recombination of short fragments as we did here, building on earlier work showing that folded hybrid domains can be generated by shuffling polypeptide segments (36). Based on prior experimental and structural studies, which include specific research in glycoside hydrolases (37,38) and whose results suggest that the common (␤␣) 8 barrel or TIM barrel evolved from an ancestral half-barrel through a series of duplication, fusion, and diversification events (20,39), our work here is in effect accelerated evolution with a particular design goal in mind. The research here is designed to combine the high substrate affinity of a mesophilic enzyme with the thermostability of a thermophilic enzyme to produce more efficient enzymes for specific substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Protein structure and function evolve through sequence changes, substitutions, duplications, 346 insertions, and deletions, including rearrangement or recombination of short fragments as we 347 did here, building on earlier work showing that folded hybrid domains can be generated by 348 shuffling polypeptide segments (38). Based on prior experimental and structural studies 349 suggesting that the common (βα) 8 reported that a stable and active chimera CelBCelCCA, which showed maximum activity at 359 70°C and was created by fusion the N-half barrel of the thermophilic CelB (maximum 360 activity at 95°C) and C-half barrel of mesophilic CelCCA (maximum activity at 50°C) (40). 361 Furthermore, Numata et al constructed chimeric isopropylmalate dehydrogenases by 362 connecting fragments from a thermophilic and a mesophilic parental enzyme.…”
Section: Discussion 345mentioning
confidence: 96%
“…Most of these hybrids produced inactive 374 proteins, and a few hybrid enzymes had partial or trace activity. Even though the previously 375 mentioned chimera CelBCelCCA displays hyperthermophile-like structural stability, the 376 chimera activity is significant lower than those of the parental enzymes CelB or CelCCA (40). 377…”
Section: Discussion 345mentioning
confidence: 96%